Making Black History : Diasporic Fiction in the Moment of Afropolitanism. - Haensell, Dominique. (Buchreihe der Anglia / Anglia Book Series, 2021)
The Anglia Book Series (ANGB) offers a selection of high quality work on all areas and aspects of English philology. It publishes book-length studies and essay collections on English language and linguistics, on English and American literature and culture from the Middle Ages to the present, on the new English literatures, as well as on general and comparative literary studies, including aspects of cultural and literary theory.